The Agriculture and Livestock Sectors’ Contribution to the Peruvian Economic Growth’s Green Classification Between 2005 and 2014 - Villavicencio, Alfredo; Tostes, Marta (European Journal of Sustainable Development, 2017)
As shown in the last NIGGE (2010), the agriculture and livestock sectors are the third most pollutant economic activities (meaning 15% of Peruvian GHG emissions), after forestry and energy. This investigation aims to provide quantitative support to the contribution of this sector to Peruvian economic growth’s green classification that can be seen through three groups of variables, applied through Ordinary Least Square regressions of data found at the Agriculture and Livestock Monthly Bulletin. As preliminary results, even though there is a positive and significant correlation between the considered Peruvian GDPs and the Environmentally Preferred Agriculture Goods, the Environmentally Non-Preferred Agriculture Goods have a higher and more significant correlation, reflecting an unsustainable trend. Moreover, Environmentally Non-Preferred Livestock Goods have a significant but reduced negative correlation with the Peruvian GDPs. On the other hand, biotrade appears as a strategy for achieving green growth due to its positive and significant correlations with the Peruvian GDPs. Finally, pesticides, fertilizers and farmed land area show non-significance in almost every result. In conclusion, through policies that reverse those trends and that foster biotrade as a green growth alternative, a significant contribution from the agriculture and livestock to the Peruvian green growth could be ultimately achieved. Keywords: Agriculture, livestock, green growth, biotrade, GHG emissions